Recent Progress in Covalent Organic Frameworks as Solid-State Ion Conductors - Li, Xing; Loh, Kian Ping (ACS materials letters, 2019)
Covalent organic frameworks (COFs) are constructed from the covalent assembly of small molecular units into periodic networks. COFs are distinguished by their crystallinity, one-dimensional channels, electrochemical stability, and ease of functionalization, thus COF-based materials have been explored for a wide range of applications over the past decade. Among these, ion conduction is receiving increasing research interests due to tailorable 1D channels and phase stability of COFs. COF ion conductors are potentially useful in fuel cells and solid-state ion batteries, but their advantages over polymer-based solid-state electrolytes remain to be discovered. In this perspective, we will discuss the pros and cons of COFs as Li-ion conductors and the possible directions to develop these materials in the future.